STUDY OF MARINE ECOTOURISM POTENTIAL IN PANDANG ISLAND SUBDISTRICT TANJUNG TIRAM NORTH SUMATERA PROVINCE - Hotdholy destrinanda; Dessy Yoswaty; Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstracEcotourism is travel to a good natural environment that is natural as well as artificial as well as cultures which are informative and participative approach that aims to ensure the sustainability of natural and socio-cultural. This research was carried out in February-March 2018 in the waters of Pandang Island,Subdistrict Tanjung Tiram, North Sumatra Province. This research aims to identify potential marine ecotourism are owned and determine the development strategy of ecotourism in the region of Island marine point of view. The methods used in this study with survey method. Index value the suitability of Tourism at setian stations namely: 91.66% I Station, station II Station 62%, III 82.69%. Judgments about strengths, weaknesses, opportunities, and threats, the development potential of the waters of the island of view assessed from the observations on site research, interviews and questionnaires.            Pandang island has the potential of marine ecotourism Standpoint with the appeal in the form of coastal ecotourism. Alternative management strategies that are appropriate for the development of marine ecotourism on the island's point of view, namely: 1) Involving the community in the supervision and management of marine ecotourism activities, supporting infrastructure Improvement 2) form of ecotourism transportation by utilizing local communities, 3) Memanfaatan the potential of natural resources, local hospitality and history to attract visitors through the concept of marine ecotourism as well as utilizing the existence of tourist attractions around the island Point of view.Kata Kunci: Potential, Ecotourism, SWOT Analysis, Pulau Pandang